Planet Zero [compact disc] (Atlantic, 2022)
An incisive look at the issues at hand: cancel culture run rampant, the corrosive effects of social media on mental health and society, and the increasingly toxic division among those of differing ideologies. Featuring Shinedown's explosive yet artfully crafted sound and urgent lyrics, it rings the alarm on a dystopian warning of the dangerous consequences to come when it all goes too far, and we begin to lose our respect for those with differing opinions and our compassion for one another.